Politik Ekonomi Islam Dalam Pengendalian Inflasi - Saparuddin Siregar (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2014)
Inflation control in Indonesia is conducted through the monetary sector by the Bank of Indonesia as monetary authority through coordination with several ministries and regional leaders by means of TPID (Tim Pengendalian Inflasi Daerah – Team to Control Regional Inflation). However, inflation remains high on average. Such situation is unwelcome for the economy, one major reason being the general reduction of societal purchasing power. This article asserts that political economic method of controlling inflation through the monetary sector which is still based on bank interest is contradictive due to its very nature of increasing inflation. This method should be slowly changed to one that is based on profit-and-loss sharing. The role played by TPID in inflation control is an ideal concept to control inflation through the creation of a perfect market, as such TPID’s seriousness is needed to execute programs which can contribute to inflation control. Society has an important role in inflation control through self-restraint based on transaction ethics. Transaction ethics is self-restrain to not increase price arbitrarily which could burden society itself. The amount of profit is indeed not limited, but it will be more socially beneficial (maslahat) when all society’s members exercise self-restraint and do not raise price of one good arbitrarily, which can lead to the increase of price of other goods and prolonged inflation.